PERANCANGAN KAPAL TANKER 12000 DWT DENGAN KECEPATAN 13 KNOT UNTUK RUTE PELAYARAN CILACAP - TELUK KABUNG - Aditya Rifki Muttaqin, (2020)
Indonesia is a maritime and archipelago country that consist of thousands of islands. This thing made an increasing in ship's needs, it is include tanker ships which have the purpose for fuel distribution in Indonesia. The fuel needs that is consump by Indonesian is highly required with the goal to support the economy and mobility of its people. Because of that, Indonesia need a credible, qualified and advanced oil transport ship so it could create a prosper society. With that matter, the design of tanker ship with 24000 dwt and speed of 13 knots for cilacap - teluk kabung sea routes hopes to be one of the solution. While conducting with the studies, design stage is to be done such as calculation of main dimensions, lines plan design, general arrangement, hydrostatic analysis, motion and stability analysis. Along with the engine and propulsion system selection which is based on the calculation of power needs and ship resistance analysis. To determine the main dimension of the ship is using the two ships comparison to get the result of the main dimension of the ship which was designed. So the results of the main dimensions of ship are length over all (LOA) = 134 m, length waterline (LWL) = 129.78, length perpandicular (LPP) = 126 m, breadth (B) = 20.5 m, height (H) = 10 m, draft (T) = 7.8 m, CB = 0.792, CM = 0.905, CW = 0.88, CP = 0.79, and service speed = 13knots.